Postglacial change of the floristic diversity gradient in Europe - Thomas Giesecke (Nature Portfolio, 2019)
Climate-induced poleward shifts in plant distributions could flatten latitudinal diversity gradients. However, here the authors show that the spread of forests after the last ice age reduced diversity in central and northern Europe, and that human land-use over the past 5000 years strengthened the latitudinal gradient in plant diversity.